Mission to Paris : a novel - Furst, Alan (Random House, 2012)
Autumn 1939. In Paris American motion picture producer Frederic Stahl is drawn into a clandestine world of foreign correspondents, exiled Spanish republicans, and spies of every sort. For as a celebrity from neutral America -- who can travel across the continent freely -- Stahl could be very useful indeed.